(untitled) (Journal of the College of Education for Women, 2021)
Deixes belong to the field of both semantics and pragmatics as they lie in the edge of these two fields. Pragmatically, they are concerned with the relationship between the structure of a language and the contexts. The present work aims at analyzing the use of deixes using Levinson’s (1983) and Yule’s (1996) concept of deixes, where the latter maintained that the referents of the deixes cannot be realized apart from the context where they are used. He added that the contextual information of certain utterances involves information about the participants (the speaker and the addressee), the time and the place. Consequently, a qualitative- descriptive approach has been adopted to meet the objective of the study which reads, “examining the 1st and 2nd person deixes in two of Pound’s lyrics ‘Girl’ and ‘A Virginal’. The study has revealed that knowledge about context affects the manifestation of the referents of deixes and uncovers the ambiguity of understanding the poetic extracts. Pragmatically speaking, the referents of the pronouns cannot be detected in isolation from the context where they are used. It has also been found that the context and the interpretation of the literary text can help in determining the referents of the deixes in terms of person, number and gender. Finally, a great relation appears when the referent of the deixis is realized in accordance with its context.